Ciclos reproductivos de la serpiente coral Micrurus nigrocinctus (Serpentes: Elapidae) en Costa Rica - Solano, Alejandro (Revista de Biología Tropical, 1988)
The coral snake Micrurus nigrocinctus has two reproductive patterns in Costa Rica. Specimens of the Pacific population (M. n. nigrocinctus) mate during the early dry season (November, January). Oviposition takes place in February and March; the mean number of eggs was 7.9 (5-14) in this population. Births occur between April and June after 47-81 days of incubation. The total length of neonates is 168-212 mm, and the weight is 1.2-2.0 g. Specimens of the Atlantic population (M. n. mosquitensis) seem to have an extended breeding season. Oviposition in this subspecies was observed in March and June; the mean number of eggs was 6.7 (5-8). Births take place in May and August, after two months of incubation. Neonates have 173189 mm in total length and 1.9-2.4 g in mass. Adult females are longer than males, especially in M. n. mosquitensis.